Enlightening grey portions of energy security towards sustainability. Issue 1 (3rd April 2017) - Soni, Vivek; Singh, Surya Prakash; Banwet, Devinder Kumar
Abstract : Purpose: The purpose of this paper is to determine priority order of Indian energy sector projects on investments and strategic dimension angles. Grey System Theory (GST) and COmplex PRroportional ASsessment (COPRAS-G) method, a flexible multi-criteria decision-making (MCDM) analyses, is used for this purpose to prioritize Indian energy sector projects, namely, coal, gas, hydro, solar and nuclear. Design/methodology/approach: The GST-based MCDM approach of COPRAS is used. Five projects of energy sector are compared based on various grey criteria. These criteria were selected on the perspectives of life-cycle costing and management-thinking approach for prioritizing these projects. The GST-based COPRAS-G is described, and results are discussed to draw a strategic road map for measuring the sustainability in the energy sector. Findings: On applying COPRAS-G on five energy projects, solar projects get high-priority order, and realistic scenario of results shows that renewable energy projects are preferred over the conventional projects such as coal and gas. Research limitations/implications: Here, COPRAS-G method is used as MCDM techniques. However, few other MCDM techniques such as fuzzy Preference Ranking Organization METHod for Enrichment Evolution, elimination and choice expressing reality and efficiency analysis technique with output satisficing can be also explored to outrank various Indian energy sector projects. Practical implications: Indian energy sector involves high degree of complexity, and, therefore, it needs more flexibility to overcome the present barriers of effective decision-making. Grey decision theory-based method like COPRAS-G is able to address energy security dimensions on different scenario of energy supply, i.e. pessimistic, optimistic and realistic, precisely. Social implications: The results can provide guidance to the government or public sector regarding various possible investment options for energy supply and can help in drawing a rough trajectory of strategy toward energy security of the country. Originality/value: This paper can supplement and act as the support for decision-making in conflicting situations specifically to have outlook of the sub-sector project on different flexible scenarios. Moreover, such work can synergize conflicting ideas of decision makers and various stakeholders of the Indian energy sector.